House Buyers' Lifestyle Segmentation Of The Housing Market In Malaysia - Foo, Fanny Suan Suan (2012)
The dynamically changing environment has created a drastic change in the lifestyle and purchase habits of the consumers. The housing development industry in Malaysia is not immune to these changes. In order to keep abreast with the shift of house buyers‘ attitude and behaviour, it is apparent that housing development companies need to do more in understanding how the house buyers think, and then satisfying their needs of the house buyers. Although the assessment lifestyle choice and preferences is a popular tool used widely in other consumer-based industries, this concept had rarely been applied in the housing development industry. To date no research had examined the lifestyle of potential house buyers for newly developed housing projects. This study aims to fill this perceived gap by identifying the segment that exists in Malaysian house buyers within the housing market as determined by their lifestyles. The model of influences on housing choice was used as the underlying theoretical framework for the study. The data were collected by way of intercept self-administered questionnaire surveys. The gathered data was then analysed by statistical tool via the SPSS version 17 Software. The respondents were grouped into five lifestyle factors namely, Appearance Oriented, Relaxed Segment, Extroverted Lifestyle, Economiser Segment and Practical Oriented house buyers.